(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the behavior of morphophysiological parameters of venerated lettuce under different layers of water and fertigation. The experiment was carried out at the Arapiraca Campus, UFAL. The design was in randomized blocks (DBC), with four blocks, arranged in a 5 x 5 factorial. The treatments consisted of five water levels (L): 50, 75, 100, 125 and 150% of the Culture Evapotranspiration (ETc), expressed in mm day-1, determined by five drainage lysimeters present in the area, correlated to five levels of fertigation: 50, 75, 100, 125, and 150. The localized drip irrigation system was used. At 30DAT, the data were collected, tabulated, and submitted to analysis of variance and the F test (P <0,05) was applied using the R software. There was an interaction of factors for the chlorophyll index a. The water levels influenced the shoot dry mass and crown diameter variables. While fertigation influenced the fresh and dry mass of the aerial part, mass, height and number of leaves. Irrigation with 50, 75, 100% of ETc can be used without affecting the morphological parameters of venerable lettuce. The higher doses of fertigation tend to implement greater return on the commercial characteristics of lettuce.